The significance of components of centralised labour quarter (CLQ) standard for workers’ housing and amenities / Muhamad Afiq bin Zully Romzi and Asmalia Che Ahmad - Zully Romzi, Muhamad Afiq; Che Ahmad, Asmalia (2019)
The introduction of the Centralised Labour Quarters (CLQ) through the Mass Rapid Transit (MRT) project is still new in the construction industry, therefore there are targets to be implemented in the long run. Unfortunately, due to the high standards given by the first MRT project, this is a burden for other construction sites to apply for in its construction area. The aim of this research is to investigate the basic needs component of CLQ standard to implement for worker housing and amenities. A questionnaire survey was conducted to seek for the significant of the component from 10 Worker Packaging Contractor (WPC). This data collection was analysed by using SPSS version 25. The result indicates that 5 out of 10 components is necessary to recommend for other construction site which are electricity, first aid and medical facilities, water, drainage, and water disposal. Majority of these findings are fit to function and comply to the Malaysian Standard (MS). However, there are several improvements proposed to further promote and develop a sustainability environment of the working housing and amenities for other CLQ.